Dilemmas in Service-Learning: (Missed) Opportunities for Transformative Partnership - Adarlo, Genejane M (Archīum Ateneo, 2019)
Although there have been growing concerns on how service-learning can accentuate the power differences between the server and the served, service-learning can foster transformative partnership by recognizing the contributions each can offer for a better society. Using participant observation and discourse analysis, this case study examines the perceptions of third-year undergraduate students of a health-related degree in a Philippine-based Jesuit university about their school–community collaboration in a primary healthcare setting. Despite apprehensions at the start of service-learning, students saw themselves confronted with the challenge to overcome personal barriers from authentically encountering the urban poor, whom they served in the community. However, establishing transformative partnership in service-learning was not without its share of dilemmas. Such findings can contribute to discourses on service-learning, informing practitioners how to support social transformation in university– community collaboration.